Modified binder for improving cycle performance of lithium battery and application thereof

A modified binder comprising reduced graphene oxide and L-ascorbyl palmitate is used to enhance the electrochemical stability and cycle life performance of lithium-ion batteries by providing a binder comprising reduced graphene oxide and L-ascorbyl palmitate is used to enhance the electrochemical stability and cycle life performance of lithium-ion batteries.

CN119242184APending Publication Date: 2025-01-03YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411442067.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The commonly used PVDF binder in lithium batteries is non-conductive, swells in traditional organic electrolytes, reduces mechanical strength, and causes environmental pollution, while existing graphene applications as a binder are limited.

Method used

A modified binder comprising reduced graphene oxide (rGO) and L-ascorbyl palmitate is used, prepared by specific annealing and microwave irradiation processes, to enhance electrochemical stability and cycle life performance.

Benefits of technology

The modified binder improves the electrochemical stability and cycle life performance of lithium-ion batteries, replacing PVDF and reducing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a modified binder for improving the cycle performance of a lithium battery and application of the modified binder, and relates to the technical field of the cycle performance of the lithium battery. According to the invention, a non-toxic and harmless weak reducing agent and L-ascorbyl palmitate are used for modifying a functionalized graphene material, and the modified functionalized graphene material is used as a lithium ion battery binder, so that the electrochemical stability, cycle life performance and the like of the lithium ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium battery cycle performance, in particular to a modified binder for improving the cycle performance of a lithium battery and application thereof. Background Art

[0002] With the massive consumption of non-renewable energy such as fossil fuels and the continuous deterioration of the ecological environment, the scientific research field around the world is actively looking for new energy development outlets to achieve sustainable development. The development of wind energy, solar energy, tidal energy, electric energy and other fields is booming. Among them, the research and development around the field of electric energy has set off a wave of enthusiasm worldwide, and the electrification process has been significantly accelerated. In the field of electric energy, energy storage devices represented by lithium-ion batteries are undergoing a new technological revolution. Lithium-ion batteries are considered to be a promising rechargeable energy storage system to replace fossil fuels due to their high energy density, long cycle life, low self-discharge, high open circuit voltage, wide operating temperature range, and green environmental protection. Binders are an indispensable component in lithium batteries.

[0003] At present, the commonly used binder in industry and laboratories is polyvinylidene fluoride (PVDF) binder. PVDF is non-conductive and will swell in traditional organic electrolytes, resulting in reduced mechanical strength. In addition, water will seriously affect the dispersion of PVDF in N-methyl-2-pyrrolidone (NMP), causing PVDF to crystallize and agglomerate in NMP, resulting in a significant decrease in bonding performance. PVDF is not absolutely stable in the electrochemical reaction environment of lithium-ion batteries, and may react with lithiated graphite, metallic lithium, etc. to produce toxic HF. At the same time, PVDF is a fluorine-containing non-biodegradable material, which may cause some environmental pollution problems. Therefore, it is very necessary to find a binder that can replace PVDF.

[0004] Graphene is a material with many excellent properties. Its high electron mobility and excellent mechanical properties make its application research in lithium-ion batteries very in-depth. Researchers mostly use graphene for negative electrodes or use graphene to modify electrode materials, but there are very few related studies on the use of graphene as a binder. The present invention uses a non-toxic and harmless weak reducing agent L-ascorbyl palmitate (LAP) to modify and modify functionalized graphene material (rGO), and uses it as a lithium-ion battery binder to improve and enhance the electrochemical stability and cycle life performance of lithium-ion batteries. Summary of the invention

[0005] The purpose of the present invention is to provide a modified binder for improving the cycle performance of a lithium battery and its application, so as to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions: A modified binder for improving the cycle performance of a lithium battery, wherein the modified binder comprises one or both of reduced graphene oxide and modified reduced graphene oxide.

[0007] The most optimized method for preparing reduced graphene oxide is to slowly inject a single-layer graphene solution into a solution containing 1 wt% CaCl 2 In aqueous solution, gel graphene is obtained; after annealing and microwave irradiation, reduced graphene oxide (rGO) is obtained.

[0008] Preferably, the concentration of the single-layer graphene solution is 0.15 g / L to 0.2 g / L; The annealing treatment parameters are: annealing treatment at 200° C. to 300° C. for 55 to 65 minutes in an argon atmosphere; the microwave irradiation process parameters are: microwave irradiation at 640W to 660W for 1 to 2s.

[0009] In the scheme, a single-layer graphene (GO) solution was slowly injected into a 1wt% CaCl 2 In aqueous solution, a uniform and continuous gel-like GO is formed by bridging the oxygen-containing groups of two GO nanosheets; then it is annealed at 300°C under argon for 1 hour to obtain slightly reduced GO, which can effectively absorb 2.45GHz microwaves; after microwave irradiation in an argon microwave oven for 1~2s, the effective absorption of microwaves causes the slightly reduced GO to heat up rapidly, resulting in the desorption of oxygen functional groups and the reordering of the graphene basal plane, obtaining reduced graphene oxide (rGO).

[0010] The more optimized preparation method of the modified reduced graphene oxide is as follows: (1) adding graphene to N-methyl-2-pyrrolidone solvent, ultrasonically dispersing, adding L-ascorbyl palmitate to prepare a suspension; (2) stirring the suspension evenly, microwave reacting, filtering, washing, and freeze-drying to obtain modified reduced graphene oxide (L-rGO).

[0011] More optimally, the ultrasonic dispersion time is 55-65 min; the stirring time is 12-13 hours; the microwave reaction conditions are: microwave reaction at 640 W-660 W for 100-120 s; and the freeze-drying time is 36-48 hours.

[0012] More optimally, the raw materials of the modified reduced graphene oxide include the following components: 100 mL of N-methyl-2-pyrrolidone, 0.1 g of graphene, and 1 g of L-ascorbyl palmitate.

[0013] An application of a modified binder for improving the cycle performance of a lithium battery, which is more optimized. The modified binder is used to prepare a pole piece. The preparation method of the pole piece is as follows: adding the modified binder to a crucible, stirring for 20±2 minutes, adding a conductive agent and an active material, stirring for 180±5 minutes in N-methyl-2-pyrrolidone, uniformly coating it on a current collector, and drying it in a vacuum drying oven at 60°C~65°C for 12~15 hours to obtain a pole piece.

[0014] More optimally, the raw materials of the electrode include: active material, modified binder, and conductive agent in a mass ratio of 8:1:1.

[0015] More optimally, the conductive agent includes conductive carbon black, and the current collector includes aluminum foil or copper foil.

[0016] More optimally, when the electrode sheet is a positive electrode sheet, the current collector is an aluminum foil, and the active material is a positive electrode material lithium iron phosphate (LFP) or a nickel-cobalt-manganese ternary material (NCM).

[0017] More optimally, when the electrode sheet is a negative electrode sheet, the current collector is a copper foil, and the active material is a negative electrode material lithium titanate (LTO).

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention can effectively improve and enhance the electrochemical stability and cycle life performance of lithium-ion batteries.

[0019] 2. The present invention provides a new type of binder for lithium battery positive electrode materials, which can replace the use of PVDF and effectively improve the environmental pollution problem caused by PVDF.

[0020] 3. PVDF is a fluorine-containing material, which is expensive and has high use cost. The present invention can effectively reduce the cost. DETAILED DESCRIPTION Example

[0022] The preparation method of modified reduced graphene oxide is as follows: (1) adding 0.1 g of graphene to 100 mL of N-methyl-2-pyrrolidone solvent, ultrasonicating for 60 min, and adding 1 g of L-ascorbyl palmitate to prepare a suspension with N-methyl-2-pyrrolidone as solvent; (2) stirring the suspension for 12 hours, microwave reacting at a power of 650 W for 120 s, and a black block-like solid substance precipitating out, filtering, washing, and freeze-drying for 36 hours to obtain modified reduced graphene oxide; The preparation method of the positive electrode sheet is as follows: adding the modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and lithium iron phosphate (positive electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on an aluminum foil (current collector), and drying it in a vacuum drying oven at 60° C. for 12 hours to obtain a positive electrode sheet; wherein the raw materials of the positive electrode sheet include: lithium iron phosphate, a modified binder, and conductive carbon black in a mass ratio of 8:1:1; The preparation method of the negative electrode sheet is as follows: adding modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and lithium titanate (negative electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on a copper foil (current collector), and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a negative electrode sheet; wherein the raw materials of the negative electrode sheet include: lithium titanate, modified binder, and conductive carbon black in a mass ratio of 8:1:1.

[0023] Example 2 is based on Example 1, the mass ratio of active material, binder and conductive agent is 9:0.5:0.5; The preparation method of modified reduced graphene oxide is as follows: (1) adding 0.1 g of graphene to 100 mL of N-methyl-2-pyrrolidone solvent, ultrasonicating for 60 min, and adding 1 g of L-ascorbyl palmitate to prepare a suspension with N-methyl-2-pyrrolidone as solvent; (2) stirring the suspension for 12 hours, microwave reacting at a power of 650 W for 120 s, and a black block-like solid substance precipitating out, filtering, washing, and freeze-drying for 36 hours to obtain modified reduced graphene oxide; The preparation method of the positive electrode sheet is as follows: adding the modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and lithium iron phosphate (positive electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on an aluminum foil (current collector), and drying it in a vacuum drying oven at 60° C. for 12 hours to obtain a positive electrode sheet; wherein the raw materials of the positive electrode sheet include: lithium iron phosphate, a modified binder, and conductive carbon black in a mass ratio of 9:0.5:0.5; The preparation method of the negative electrode sheet is as follows: adding modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and lithium titanate (negative electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on a copper foil (current collector), and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a negative electrode sheet; wherein the raw materials of the negative electrode sheet include: lithium titanate, modified binder, and conductive carbon black in a mass ratio of 9:0.5:0.5.

[0024] Example 3 is based on Example 1, the mass ratio of active material, binder and conductive agent is 9.2:0.5:0.3; The preparation method of modified reduced graphene oxide is as follows: (1) adding 0.1 g of graphene to 100 mL of N-methyl-2-pyrrolidone solvent, ultrasonicating for 60 min, and adding 1 g of L-ascorbyl palmitate to prepare a suspension with N-methyl-2-pyrrolidone as solvent; (2) stirring the suspension for 12 hours, microwave reacting at a power of 650 W for 120 s, and a black block-like solid substance precipitating out, filtering, washing, and freeze-drying for 36 hours to obtain modified reduced graphene oxide; The preparation method of the positive electrode sheet is as follows: adding the modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and lithium iron phosphate (positive electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on an aluminum foil (current collector), and drying it in a vacuum drying oven at 60° C. for 12 hours to obtain a positive electrode sheet; wherein the raw materials of the positive electrode sheet include: lithium iron phosphate, a modified binder, and conductive carbon black in a mass ratio of 9.2:0.5:0.3; The preparation method of the negative electrode sheet is as follows: adding modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and lithium titanate (negative electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on a copper foil (current collector), and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a negative electrode sheet; wherein the raw materials of the negative electrode sheet include: lithium titanate, modified binder, and conductive carbon black in a mass ratio of 9.2:0.5:0.3. Example

[0025] The preparation method of modified reduced graphene oxide is as follows: (1) adding 0.1 g of graphene to 100 mL of N-methyl-2-pyrrolidone solvent, ultrasonicating for 60 min, and adding 1 g of L-ascorbyl palmitate to prepare a suspension with N-methyl-2-pyrrolidone as solvent; (2) stirring the suspension for 12 hours, microwave reacting at a power of 650 W for 120 s, and a black block-like solid substance precipitating out, filtering, washing, and freeze-drying for 36 hours to obtain modified reduced graphene oxide; The preparation method of the positive electrode sheet is as follows: adding the modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and nickel-cobalt-manganese ternary material (positive electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on an aluminum foil (current collector), and drying it in a vacuum drying oven at 60° C. for 12 hours to obtain a positive electrode sheet; wherein the raw materials of the positive electrode sheet include: nickel-cobalt-manganese ternary material, modified binder, and conductive carbon black in a mass ratio of 8:1:1; The preparation method of the negative electrode sheet is as follows: adding modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and lithium titanate (negative electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on a copper foil (current collector), and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a negative electrode sheet; wherein the raw materials of the negative electrode sheet include: lithium titanate, modified binder, and conductive carbon black in a mass ratio of 8:1:1.

[0026] Example 5 is based on Example 4, the mass ratio of active material: binder: conductive agent is 9:0.5:0.5; The preparation method of modified reduced graphene oxide is as follows: (1) adding 0.1 g of graphene to 100 mL of N-methyl-2-pyrrolidone solvent, ultrasonicating for 60 min, and adding 1 g of L-ascorbyl palmitate to prepare a suspension with N-methyl-2-pyrrolidone as solvent; (2) stirring the suspension for 12 hours, microwave reacting at a power of 650 W for 120 s, and a black block-like solid substance precipitating out, filtering, washing, and freeze-drying for 36 hours to obtain modified reduced graphene oxide; The preparation method of the positive electrode sheet is as follows: adding the modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and nickel-cobalt-manganese ternary material (positive electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on an aluminum foil (current collector), and drying it in a vacuum drying oven at 60° C. for 12 hours to obtain a positive electrode sheet; wherein the raw materials of the positive electrode sheet include: nickel-cobalt-manganese ternary material, modified binder, and conductive carbon black in a mass ratio of 9:0.5:0.5; The preparation method of the negative electrode sheet is as follows: adding modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and lithium titanate (negative electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on a copper foil (current collector), and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a negative electrode sheet; wherein the raw materials of the negative electrode sheet include: lithium titanate, modified binder, and conductive carbon black in a mass ratio of 9:0.5:0.5.

[0027] Example 6 is based on Example 4, the mass ratio of active material: modified binder: conductive agent is 9.2:0.5:0.3; The preparation method of modified reduced graphene oxide is as follows: (1) adding 0.1 g of graphene to 100 mL of N-methyl-2-pyrrolidone solvent, ultrasonicating for 60 min, and adding 1 g of L-ascorbyl palmitate to prepare a suspension with N-methyl-2-pyrrolidone as solvent; (2) stirring the suspension for 12 hours, microwave reacting at a power of 650 W for 120 s, and a black block-like solid substance precipitating out, filtering, washing, and freeze-drying for 36 hours to obtain modified reduced graphene oxide; The preparation method of the positive electrode sheet is as follows: adding the modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and nickel-cobalt-manganese ternary material (positive electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on an aluminum foil (current collector), and drying it in a vacuum drying oven at 60° C. for 12 hours to obtain a positive electrode sheet; wherein the raw materials of the positive electrode sheet include: nickel-cobalt-manganese ternary material, modified binder, and conductive carbon black in a mass ratio of 9.2:0.5:0.3; The preparation method of the negative electrode sheet is as follows: adding modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and lithium titanate (negative electrode material), stirring in N-methyl-2-pyrrolidone for 3 hours, uniformly coating it on a copper foil (current collector), and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a negative electrode sheet; wherein the raw materials of the negative electrode sheet include: lithium titanate, modified binder, and conductive carbon black in a mass ratio of 9.2:0.5:0.3.

[0028] Comparative Example 1 is based on Example 1, and the binder uses PVDF; The preparation method of the positive electrode sheet is as follows: adding PVDF into a crucible, stirring for 20 minutes, adding conductive carbon black and lithium iron phosphate (positive electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on an aluminum foil (current collector), and drying it in a vacuum drying oven at 60° C. for 12 hours to obtain a positive electrode sheet; wherein the raw materials of the positive electrode sheet include: lithium iron phosphate, PVDF, and conductive carbon black in a mass ratio of 8:1:1; The preparation method of the negative electrode sheet is as follows: adding modified reduced graphene oxide into a crucible, stirring for 20 minutes, adding conductive carbon black and lithium titanate (negative electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on a copper foil (current collector), and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a negative electrode sheet; wherein the raw materials of the negative electrode sheet include: lithium titanate, PVDF, and conductive carbon black in a mass ratio of 8:1:1.

[0029] Comparative Example 2 is based on Example 1, and rGO is used as the binder; The preparation method of reduced graphene oxide is: slowly injecting a single-layer graphene solution into a solution containing 1wt% CaCl 2 In aqueous solution, gel graphene was obtained; annealed in an argon atmosphere at 300°C for 60 minutes, and microwaved for 2 seconds at a power of 650W to obtain reduced graphene oxide (rGO); wherein the concentration of the single-layer graphene solution was 0.2g / L; The preparation method of the positive electrode sheet is as follows: add rGO into a crucible, stir for 20 minutes, add conductive carbon black and lithium iron phosphate (positive electrode material), stir in N-methyl-2-pyrrolidone for 180 minutes, evenly coat it on aluminum foil (current collector), and dry it in a vacuum drying oven at 60°C for 12 hours to obtain a positive electrode sheet; wherein the raw materials of the positive electrode sheet include: lithium iron phosphate, rGO, and conductive carbon black in a mass ratio of 8:1:1; The preparation method of the negative electrode sheet is as follows: add rGO into a crucible, stir for 20 minutes, add conductive carbon black and lithium titanate (negative electrode material), stir in N-methyl-2-pyrrolidone for 180 minutes, evenly coat it on a copper foil (current collector), and dry it in a vacuum drying oven at 60°C for 12 hours to obtain a negative electrode sheet; wherein the raw materials of the negative electrode sheet include: lithium titanate, rGO, and conductive carbon black in a mass ratio of 8:1:1.

[0030] Comparative Example 3 is based on Example 4, and the binder uses PVDF; The preparation method of the positive electrode sheet is as follows: adding PVDF into a crucible, stirring for 20 minutes, adding conductive carbon black and nickel-cobalt-manganese ternary material (positive electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on an aluminum foil (current collector), and drying it in a vacuum drying oven at 60° C. for 12 hours to obtain a positive electrode sheet; wherein the raw materials of the positive electrode sheet include: nickel-cobalt-manganese ternary material, PVDF, and conductive carbon black in a mass ratio of 8:1:1; The preparation method of the negative electrode sheet is as follows: adding PVDF into a crucible, stirring for 20 minutes, adding conductive carbon black and lithium titanate (negative electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on a copper foil (current collector), and drying it in a vacuum drying oven at 60°C for 12 hours to obtain a negative electrode sheet; wherein the raw materials of the negative electrode sheet include: lithium titanate, PVDF, and conductive carbon black in a mass ratio of 8:1:1.

[0031] Comparative Example 4 is based on Example 4, and rGO is used as the binder; The preparation method of reduced graphene oxide is: slowly injecting a single-layer graphene solution into a solution containing 1wt% CaCl 2 In aqueous solution, gel graphene was obtained; annealed in an argon atmosphere at 300°C for 60 minutes, and microwaved for 2 seconds at a power of 650W to obtain reduced graphene oxide (rGO); wherein the concentration of the single-layer graphene solution was 0.2g / L; The preparation method of the positive electrode sheet is as follows: adding rGO into a crucible, stirring for 20 minutes, adding conductive carbon black and nickel-cobalt-manganese ternary material (positive electrode material), stirring in N-methyl-2-pyrrolidone for 180 minutes, uniformly coating it on an aluminum foil (current collector), and drying it in a vacuum drying oven at 60° C. for 12 hours to obtain a positive electrode sheet; wherein the raw materials of the positive electrode sheet include: nickel-cobalt-manganese ternary material, rGO, and conductive carbon black in a mass ratio of 8:1:1; The preparation method of the negative electrode sheet is as follows: add rGO into a crucible, stir for 20 minutes, add conductive carbon black and lithium titanate (negative electrode material), stir in N-methyl-2-pyrrolidone for 180 minutes, evenly coat it on a copper foil (current collector), and dry it in a vacuum drying oven at 60°C for 12 hours to obtain a negative electrode sheet; wherein the raw materials of the negative electrode sheet include: lithium titanate, rGO, and conductive carbon black in a mass ratio of 8:1:1.

[0032] Detection test: Assembled battery: The battery used in the present invention is a CR2032 button cell; a polypropylene microporous membrane (Celgard 2400) is used as the separator of the lithium-ion battery, a lithium sheet is used as the counter electrode, and the electrolyte is 1.0M LiPF dissolved in a mixed solution of EC:DMC:EMC=1:1:1 vol% 6 ; Assemble the battery in a glove box filled with high-purity argon to ensure that the water and oxygen content in the glove box is less than 0.5 ppm. The assembly order of the battery is as follows: (1) Assemble in an inert atmosphere glove box to prevent moisture and oxygen in the environment from affecting the battery performance. First, lay the negative electrode shell flat, place the negative electrode sheet in the center of the negative electrode shell, and use a tablet pressing mold to flatten the metal lithium sheet; (2) Lay the diaphragm flat on the upper layer of the negative electrode sheet, use a pipette to take an appropriate amount of electrolyte and drop it on the surface of the diaphragm; (3) Use insulating tweezers to place the positive electrode sheet, gasket, spring sheet and positive electrode shell on the upper layer of the diaphragm in turn, where the active material side of the positive electrode sheet must be close to the diaphragm; (4) Use insulating tweezers to place the button battery with the negative side facing up on the button battery sealing machine mold. A paper towel can be placed on the top of the battery to absorb the overflowed electrolyte, and the pressure is adjusted to complete the assembly. After assembly, take the assembled battery out of the glove box, press the battery with a tablet press, and set it aside for 12 hours.

[0033] The battery's cycle performance was tested using the voltammetric cycle test method. The test results are shown in Table 1: Table 1

[0034] Conclusion: In Table 1, the data of Example 1 is compared with that of Example 2 and Example 3, and the data of Example 4 and Example 5 and Example 6 are compared. It can be found that under long cycle, in lithium iron phosphate batteries and ternary batteries, when the active material: binder: conductive agent = 8:1:1, the battery capacity retention rate is the highest; by comparing the data of Example 1 and Comparative Example 2 and Comparative Example 3, in lithium iron phosphate batteries, when L-rGO is used as the binder, the battery capacity retention rate is increased by more than 10%; by comparing the data of Example 4 and Comparative Example 5 and Comparative Example 6, in ternary batteries, when L-rGO is used as the binder, the battery capacity retention rate is also increased by more than 10%; based on the above data, it can be explained that when L-rGO is used as a binder for the positive electrode material of the battery (in LFP and NCM systems), the cycle performance of the battery can be greatly improved.

[0035] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A modified binder for improving the cycle performance of a lithium battery, characterized in that: The modified binder includes one or both of reduced graphene oxide and modified reduced graphene oxide.

2. A modified binder for improving the cycle performance of a lithium battery according to claim 1, characterized in that: The preparation method of the reduced graphene oxide comprises: slowly injecting a single-layer graphene solution into an aqueous solution containing 1 wt% of CaCl2 to obtain gel-like graphene; and performing annealing treatment and microwave irradiation to obtain the reduced graphene oxide.

3. A modified binder for improving the cycle performance of a lithium battery according to claim 2, characterized in that: The concentration of the single-layer graphene solution is 0.15 g / L to 0.2 g / L; The annealing treatment parameters are: annealing treatment at 200-300° C. for 55-65 min in an argon atmosphere; the microwave irradiation process parameters are: microwave irradiation at 640 W-660 W for 1-2 s.

4. The modified binder for improving the cycle performance of a lithium battery according to claim 1, characterized in that: The preparation method of the modified reduced graphene oxide is as follows: (1) adding graphene to N-methyl-2-pyrrolidone solvent, ultrasonically dispersing, and adding L-ascorbyl palmitate to prepare a suspension; (2) stirring the suspension evenly, microwave reacting, filtering, washing, and freeze-drying to obtain the modified reduced graphene oxide.

5. A modified binder for improving the cycle performance of a lithium battery according to claim 4, characterized in that: The ultrasonic dispersion time is 55-65 minutes; the stirring time is 12-13 hours; the microwave reaction conditions are: microwave reaction at 640W-660W for 100-120s; and the freeze-drying time is 36-48 hours.

6. A modified binder for improving the cycle performance of a lithium battery according to claim 4, characterized in that: The raw materials of the suspension include the following components: 100 mL of N-methyl-2-pyrrolidone, 0.1 g of graphene, and 1 g of L-ascorbyl palmitate.

7. The use of a modified binder for improving the cycle performance of a lithium battery according to any one of claims 1 to 6, characterized in that: The modified binder is used to prepare a pole piece: the modified binder, a conductive agent, and an active material are uniformly mixed in N-methyl-2-pyrrolidone, and the mixture is uniformly coated on a current collector, and the pole piece is obtained after drying.

8. The use of a modified binder for improving the cycle performance of a lithium battery according to claim 7, characterized in that: When the electrode sheet is a positive electrode sheet, the current collector is aluminum foil, and the active material is a positive electrode material such as lithium iron phosphate or a nickel-cobalt-manganese ternary material.

9. The use of a modified binder for improving the cycle performance of a lithium battery according to claim 7, characterized in that: When the electrode sheet is a negative electrode sheet, the current collector is copper foil, and the active material is the negative electrode material lithium titanate.